DEAR (DIGITAL EXPLORATION CAREER): HYPERMEDIA-BASED INNOVATION MEDIA FOR GUINDANCE AND COUNSELING TO EXPLORE STUDENT CAREER IN THE INDUSTRIAL REVOLUTION 4.0 - Bayu Selo Aji; Cucu Kurniasih; Berlin Fanta Rosiani; Caraka Putra Bhakti (International Journal of Educational Management and Innovation, 2020)
This scientific work aims to provide creative innovations in guidance and counseling services using the BK media to explore student careers. Entering the era of the Industrial Revolution 4.0, students today must have the ability and skills to predict a rapidly changing future, especially concerning career problems. Guidance and Counseling Teachers here play an essential role in developing students' potential, and one way is to optimize the role of Guidance and Counseling in schools by optimizing services about career exploration. For support services on career exploration, BK (Guidance and Counseling) media needed to improve students' understanding of the services provided. One of them uses DEAR (Digital Exploration Career) based media as an alternative and innovation that can use to explore students' careers. DEAR (Digital Exploration Career) is a hypermedia-based BK media. Each use of this media in service delivery also pays attention to students' needs, materials, entertainment, and evaluations so that the media is effective in service delivery even though sometimes without face to face. So that this media provides a new atmosphere and innovation in the provision of BK services so that they can run dynamically by the times. Then DEAR (Digital Exploration Career) Hypermedia-Based Bk Media Innovation is one solution that can use to explore students' careers in the industrial revolution era 4.0